The Attitudes of School Directors to the Multicultural Education in Turkey - POLAT, Soner (Mediterranean Journal of Social Sciences, 2011)
The aim of this research, to determine the attitude of school directors to the multicultural education. The date of the research inthe descriptive survey model was collected with the multicultural education attitude scale. The population of the research consists of theschool directors which belong to public in the city of Kocaeli, and its sampling consists of 209 school directors which were appointed to theheadship for the first time in 2009-2010 academic years. At the end of the research it was found out that the school directors had apositive attitude to the multicultural education. While the gender factor does not make a significant difference in the attitudes of the schooldirectors to the multicultural education, educational level, age and seniority has made a significant difference in the attitude to themulticultural education. While the decrease is observed in the attitude to the multicultural education when age and seniority increases, theincrease has been observed in the attitude to the multicultural education when the educational level increases.